Differences in Mediterranean diet adherence on lipid profile and plasma atherogenic index in dyslipidemia patients - Dewi R Handayani; Khomaini Hasan; Iis I Rakhmat; Endry Septiadi; Yudith Y Kusmala (ACTA Medical Health Sciences, 2022)
Dyslipidemia is a lipid metabolism disorder characterized by an increase in total cholesterol, triglycerides, and Low-Density Lipoprotein (LDL), as well as a decrease in High-Density Lipoprotein (HDL). According to the 2018 Basic Health Research (Riset Kesehatan Dasar/RISKESDAS), 12.6% of the Indonesian population aged 55–64 years had high cholesterol levels along with very high LDL and triglyceride levels. The Mediterranean diet is a form of non-pharmacological therapy involving nutritional intervention for patients with dyslipidemia. This study aimed to examine the effect of adherence to the Mediterranean diet on lipid profiles and the Plasma Atherogenic Index (PAI) in dyslipidemic patients at a private clinic in Bandung. This research employed an observational analytic method with a prospective cohort design involving 30 patients with dyslipidemia. Subjects were selected using a systematic random sampling technique and categorized into three groups based on their adherence to the Mediterranean diet: low, medium, and high. At the end of the month, lipid profile parameters and PAI were measured. Data on total cholesterol, LDL, and HDL levels were analyzed using ANOVA and Tukey’s Post Hoc test, while triglycerides and PAI were analyzed using the Kruskal-Wallis and Mann-Whitney tests. The results showed significant differences in total cholesterol (p = 0.007), LDL (p = 0.019), HDL (p = 0.006), triglycerides (p = 0.005), and PAI (p = 0.036) across the adherence groups. These findings suggest that higher adherence to the Mediterranean diet is associated with improvements in lipid profile and PAI. The beneficial effects are likely due to the diet’s rich content of monounsaturated fatty acids (MUFA), polyunsaturated fatty acids (PUFA), phytosterols, and polyphenols, which positively influence lipid metabolism and reduce atherogenic risk. DOI : 10.35990/amhs.v1n1.p1-9 REFERENCES Jameson JL. Harrison’s Principles of Internal Medicine. Edisi ke-19. Kasper DL, editor. New York: McGraw-Hill; 2015. hlm. 2438. John MF, Adam. Dislipidemia. Dalam: Sudoyo AW, dkk., editor. Buku Ajar Penyakit Dalam. Edisi IV. Jakarta: Balai Penerbit Departemen Ilmu Penyakit Dalam FKUI; 2006. hlm. 2554. Gebreegziabiher G, Belachew T, Mehari K, Tamiru D. Prevalence of dyslipidemia and associated risk factors among adult residents of Mekelle City, Northern Ethiopia. PLoS One. 2021;16:1–18. Qi L, Ding X, Tang W, Li Q, Mao D, Wang Y. Prevalence and risk factors associated with dyslipidemia in Chongqing, China. Int J Environ Res Public Health. 2015;12(10):13455–65. Roslaeni R, Sundari R, Baswedan MH. Gambaran Risiko Penyakit Jantung Koroner Berdasarkan Rasio Profil Lipid Pada Usia Dewasa Muda. Med Kartika J Kedokt dan Kesehat. 2019;2(2):110–22. Millán J, Pintó X, Muñoz A, Zúñiga M, Rubiés-Prat J, Pallardo LF, et al. Lipoprotein ratios: Physiological significance and clinical usefulness in cardiovascular prevention. Vasc Health Risk Manag. 2009;5:757–65. Arsana PM, Rosandi R, Manaf A, Budhiarta A, Permana H. Pedoman Pengelolaan Dislipidemi di Indonesia 2019. PB PERKENI; 2019. hlm. 9. Perhimpunan Dokter Spesialis Kardiovaskular Indonesia. Panduan Tatalaksana Dislipidemia. 2017. Van Horn L, Carson JAS, Appel LJ, Burke LE, Economos C, Karmally W, et al. Recommended dietary pattern to achieve adherence to the AHA/ACC Guidelines: A scientific statement from the American Heart Association. Circulation. 2016;134(22):505–29. Liyanage T, Ninomiya T, Wang A, Neal B, Jun M, Wong MG, et al. Effects of the Mediterranean diet on cardiovascular outcomes: A systematic review and meta-analysis. PLoS One. 2016;11(8). Anggraini DI, Labibah Z. Diet Mediterania dan Manfaatnya terhadap Kesehatan Jantung dan Kardiovaskular. J Major. 2016;5(3):1–3. Jacobs S, Harmon BE, Ollberding NJ, Wilkens LR, Monroe KR, Kolonel LN, et al. Among 4 diet quality indexes, only the alternate Mediterranean diet score is associated with better colorectal cancer survival and only in African American women in the Multiethnic Cohort. J Nutr. 2016;146(9):1746–55. Tian HY, Qiu R, Jing LP, Chen ZY, Chen GD, Chen YM. Alternate Mediterranean diet score is positively associated with skeletal muscle mass index in middle-aged adults. Br J Nutr. 2017;117(8):1181–8. Shvetsov YB, Harmon BE, Ettienne R, Wilkens LR, Le Marchand L, Kolonel LN, et al. The influence of energy standardisation on the alternate Mediterranean diet score and its association with mortality in the Multiethnic Cohort. Br J Nutr. 2016;116(9):1592–601. Feng L, Nian S, Tong Z, Zhu Y, Li Y, Zhang C, et al. Age-related trends in lipid levels: A large-scale cross-sectional study of the general Chinese population. BMJ Open. 2020;10(3):e034226. Liu HH, Li JJ. Aging and dyslipidemia: A review of potential mechanisms. Ageing Res Rev. 2015;19:43–52. DG I, Shetty S, Rao AV, Ahmad S. Age-related difference in the lipid profile in normal healthy women. J Health Allied Sci NU. 2014;4(2):94–7. Palmisano BT, Zhu L, Stafford JM. Role of estrogens in the regulation of liver lipid metabolism. In: Advances in Experimental Medicine and Biology. Vol. 1043. 2017. hlm. 227–56. Schwingshackl L, Morze J, Hoffmann G. Mediterranean diet and health status: Active ingredients and pharmacological mechanisms. Br J Pharmacol. 2020;177(6):1241–57. Poli A, Marangoni F, Corsini A, Manzato E, Marrocco W, Martini D, et al. Phytosterols, cholesterol control, and cardiovascular disease. Nutrients. 2021;13(8):1–13. Castro-Barquero S, Lamuela-Raventós RM, Doménech M, Estruch R. Relationship between Mediterranean dietary polyphenol intake and obesity. Nutrients. 2018;10(10):1–13. Ferro Y, Mazza E, Salvati M, Santariga E, Giampà S, Spagnuolo R, et al. Effects of a portfolio-Mediterranean diet and a Mediterranean diet with or without a sterol-enriched yogurt in individuals with hypercholesterolemia. Endocrinol Metab. 2020;35(2):298–307. Hannon BA, Thompson SV, An R, Teran-Garcia M. Clinical outcomes of dietary replacement of saturated fatty acids with unsaturated fat sources in adults with overweight and obesity: A systematic review and meta-analysis of randomized control trials. Ann Nutr Metab. 2017;71:107–17. Hernáez Á, Fernández-Castillejo S, Farràs M, Catalán Ú, Subirana I, Montes R, et al. Olive oil polyphenols enhance high-density lipoprotein function in humans: A randomized controlled trial. Arterioscler Thromb Vasc Biol. 2014;34(9):2115–9. Grao-Cruces E, Varela LM, Martin ME, Bermudez B, Montserrat-De la Paz S. High-density lipoproteins and Mediterranean diet: A systematic review. Nutrients. 2021;13(3):1–11. Alves-Bezerra M, Cohen DE. Triglyceride metabolism in the liver. Compr Physiol. 2018;8(1):1–22. Betaubun AM, Bahrun U, Pakasi R. Indeks Aterogenik Plasma di Penyakit Diabetes Melitus Tipe 2 (Atherogenic Index of Plasma in Type 2 Diabetes Mellitus). Indones J Clin Pathol Med Lab. 2018;22(1):82.